Blended learning and digital curation: A learning design sequence - Ostashewski, N.; Martin, R.; Brennan, Andrew (2015)
© 2015, IGI Global.This chapter presents a case of successful integration of digital curation in a repeating series of blended classroom activities. Digital curation, in education, can be understood as the collection, organization, interpretation, summary, and sharing of online resources by learners on a topic of inquiry. This research reports on a blended digital curation learning design integrated into a third-year university course. A digital curation activity sequence development process and the classroom activity structure form the basis of the educational implementation presented here. In theory, digital curation activities can support the sharing of collected resources between learners. In practice, digital curation learning activities in higher education can also support blended and flipped classroom engagement models while providing opportunities for the development of critical thinking skills. The chapter describes the activities, the learning design, and the outcomes of a digital curation activity sequence. This provides other educators with a learning design roadmap for engaging students in pre-lecture activities or blended learning that adds value to classroom lectures.